MiR-221-3p promotes hepatocellular carcinogenesis by downregulating O6-methylguanine-DNA methyltransferase. Issue 10 (2nd October 2020) - Chen, Zushun; Xiang, Bangde; Qi, Lunan; Zhu, Shaoliang; Li, Lequn
ABSTRACT: This study aimed to investigate the influence of miR-221-3p and O 6 -methylguanine-DNA methyltransferase (MGMT) interaction in human hepatocellular carcinoma (HCC), thereby revealing a novel molecular mechanism of hepatic carcinogenesis involving miR-221-3p and MGMT. Fluorescence qPCR and immunoblot assays were performed to determine the expression of RNA and protein in HCC tissues and cell lines. We also employed the firefly and Renilla luciferase assay to verify the target relationship between miR-221-3p and MGMT mRNA. Assessments including the MTT assay, wound-healing assay, transwell assay, colony foci formation experiment, and flow cytometric experiment were carried out to determine the viability, migration, invasion, proliferation, cell cycle progression, and apoptosis of SMMC-7721 and BEL-7404 cell lines with the modulated expression of miR-221-3p and MGMT. Compared to healthy tissues and cell line HL7702, miR-221-3p was significantly upregulated but MGMT was significantly downregulated in carcinomas and cancerous cell lines. Forced miR-221-3p overexpression was found to enhance the proliferation, migration, invasion, and clonogenicity of cell lines, but it suppressed cell apoptosis. Findings also revealed that forced miR-221-3p overexpression had little effect on cell cycle progression. After MGMT was confirmed to be atarget gene of miR-221-3p, it was found that the forced upregulation of miR-221-3p downregulated MGMT mRNA and protein levels significantly. MiR-221-3p was identified as an HCC promoting factor, and it specifically inhibited the expression of the MGMT. Besides, the upregulation of miR-221-3p had apositive influence on HCC pathogenesis by inhibiting MGMT expression.